A diagnostic kit for the detection of early acute leptospirosis - Bahaman, Abdul Rani; Seenichamy, Arivudainambi (2011)
The present invention relates to a diagnostic method for the detection of acute leptospirosis. The method of the invention allows for a quick, specific and sensitive detection of the disease caused by pathogenic Leptospira. The described method is based on the immunological detection of the protein LipL21, a membrane protein expressed specifically by pathogenic strains of Leptospira. Furthermore, the present invention relates to the development of a diagnostic device that allows positive diagnosis to be conducted in the early and critical stage of the infection. The preferred diagnostic device of the invention is a lateral flow test, which as a hand-held assay, is easy to use and facilitates diagnosis of leptospirosis in the first 5 days of infection. Further disclosed is the antibody raised against the LipL21 protein as well as its respective uses in the diagnostic methods and devices. Finally, a diagnostic kit is disclosed containing the inventive materials described herein to conduct diagnosis of acute leptospirosis during the critical early stage of infection. The first 5 days of the infection is where the subject or patient could succumb to the disease. Diagnosis of the disease at this critical stage of infection would then advise the affected patient to have immediate systemic antibiotic treatment and thereby, avoid succumbing to the disease.